Head impacts in a junior rugby league team measured with a wireless head impact sensor: an exploratory analysis - King, D.; Hume, P.; Gissane, C.; Clark, T. (Journal of Neurosurgery: Pediatrics, 2016)
OBJECTIVE The aim of this study was to investigate the frequency, magnitude, and distribution of head impacts sustained by players in a junior rugby league over a season of matches. METHODS The authors performed a prospective cohort analysis of impact magnitude, frequency, and distribution on data collected with instrumented XPatches worn behind the ear of players in an "under-11" junior rugby league team (players under 11 years old). RESULTS A total of 1977 impacts were recorded. Over the course of the study, players sustained an average of 116 impacts (average of 13 impacts per player per match). The measured linear acceleration ranged from 10g to 123g (mean 22g, median 16g, and 95th percentile 57g). The rotational acceleration ranged from 89 rad/sec2 to 22,928 rad/sec2 (mean 4041 rad/sec2, median 2773 rad/sec2, and 95th percentile 11,384 rad/sec2). CONCLUSIONS The level of impact severity based on the magnitude of impacts for linear and rotational accelerations recorded was similar to the impacts reported in studies of American junior and high school football, collegiate football, and youth ice hockey players, but the players in the rugby league cohort were younger, had less body mass, and played at a slower speed than the American players. Junior rugby league players are required to tackle the player to the ground and use a different tackle technique than that used in American football, likely increasing the rotational accelerations recorded at the head.